ANALISIS PROSES BELAJAR SISWA KELAS IV SD DALAM MEMAHAMI PERAN SOSIAL MELALUI PROYEK BAKUTOLONG DENGAN PENDEKATAN KONSTRUKTIVISME DI WILAYAH PERBATASAN KALIMANTAN UTARA - Sisca Ayu Azhari; Rusi Rusmiati Aliyyah (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
This study aims to analyze the learning process of fourth-grade students at SD Negeri 003 Sei Menggaris in understanding the concept of social roles through the Bakutolong project using a constructivist approach. The primary problem underlying this research is the difficulty students encounter in comprehending abstract social role theories. This study employed a descriptive qualitative method involving 26 students as respondents. Data were collected through observation, in-depth interviews with three students (MA, NFR, and T), and learning achievement tests, then analyzed using the Miles and Huberman model encompassing data reduction, data presentation, and conclusion drawing, with source, method, and theory triangulation applied throughout.The findings reveal that the constructivist approach implemented through a real-action project was effective in fostering students' understanding. Students were able to construct the meaning of social roles as a shared responsibility rather than merely memorizing theoretical concepts, as evidenced by an observation score of 90.35%, classified as highly effective, and a learning completion rate of 88.46%. The Bakutolong project successfully transformed students' perspectives, turning them into agents of change within the school environment. This study concludes that the integration of local wisdom within a constructivist framework generates contextual, interactive, and meaningful learning experiences for elementary school students. ABSTRAK Penelitian ini bertujuan menganalisis proses belajar siswa kelas IV SD Negeri 003 Sei Menggaris dalam memahami konsep peran sosial melalui proyek Bakutolong dengan pendekatan konstruktivisme. Masalah utama yang melatarbelakangi penelitian ini adalah sulitnya siswa memahami teori peran sosial yang bersifat abstrak. Penelitian menggunakan metode kualitatif deskriptif dengan melibatkan 26 siswa sebagai responden. Data dikumpulkan melalui observasi, wawancara mendalam kepada tiga siswa (MA, NFR, dan T), serta tes hasil belajar, dan dianalisis menggunakan model Miles dan Huberman melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan dengan triangulasi sumber, metode, dan teori. Hasil penelitian menunjukkan bahwa pendekatan konstruktivisme melalui proyek aksi nyata efektif membangun pemahaman siswa. Siswa mampu mengonstruksi makna peran sosial sebagai tanggung jawab bersama, bukan sekadar menghafal teori, dibuktikan dengan hasil observasi sebesar 90,35% berkriteria sangat efektif dan ketuntasan belajar mencapai 88,46%. Proyek Bakutolong berhasil mengubah persepsi siswa menjadi agen perubahan di lingkungan sekolah. Simpulan penelitian ini adalah integrasi kearifan lokal dalam bingkai konstruktivisme menciptakan pembelajaran yang kontekstual, interaktif, dan bermakna bagi siswa sekolah dasar.